2021
DOI: 10.3390/microorganisms9102113
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Activity of Ziziphus spina-christi Leaves Extract and Its Possible Cellular Mechanisms

Abstract: This experimental investigation was designed to assess the in vitro and in vivo antileishmanial effects of Z. spina-christi methanolic extract (ZSCME) and also aims to assess some of the antileishmanial mechanisms such as the NO production, apoptosis, and plasma membrane permeability. We assessed the in vitro leishmanicidal effects of ZSCME (10–200 µg/mL) against intracellular amastigote stage of the Leishmania major (MRHO/IR/75/ER) and, then, in vivo examined male BALB/c mice infected by L. major. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The leaves obtained from Indonesia [ 29 , 83 ] as well as other parts of the world [ 70 , 85 ], were reported to have shown the presence of flavonoids, alkaloids, saponins, tannins, steroids, and triterpenes. The presence of monosaccharides, reducing sugars, pentose, ketosis, deoxy sugars, and indole alkaloids were reported in the leaves collected from the Plateau state, Nigeria [ 122 , 164 ]. The detection of glycosides in the aerial parts and cardiac glycoside in the leaves was also reported [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaves obtained from Indonesia [ 29 , 83 ] as well as other parts of the world [ 70 , 85 ], were reported to have shown the presence of flavonoids, alkaloids, saponins, tannins, steroids, and triterpenes. The presence of monosaccharides, reducing sugars, pentose, ketosis, deoxy sugars, and indole alkaloids were reported in the leaves collected from the Plateau state, Nigeria [ 122 , 164 ]. The detection of glycosides in the aerial parts and cardiac glycoside in the leaves was also reported [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Difference in geographical location has been noted to influence the biosynthesis and accumulation of secondary metabolites in plants. In the aerial parts collected in Tabuk, Saudi Arabia [ 122 ], and fruits and seeds collected in Qena city, Egypt [ 75 ], saponin was reportedly absent. Studies on the bark, fruit, root, seed, and leaf extracts were reported to have shown the presence of steroids, flavonoids, tannins, and alkaloids, but absence of triterpenes [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The solution was then passed through a Whatman filter paper and concentrated at 55°C under vacuum conditions using a rotary evaporator (Heidolph, Schwabach, Germany). The lyophilized extract was preserved at −20°C until testing ( Albalawi, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed CZME for the presence of phytochemicals such as terpenoids, flavonoids, saponins, alkaloids, and tannins using some qualitative experiments explained previously ( Albalawi, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Three hundred grams of the dried leaves were extracted by percolation method using 70% methanol for 72 h at 21°C. Extract was then filtered by filter paper and concentrated in vacuum condition at 55°C using a rotary evaporator (Heidolph, Germany) and kept at -20°C until testing (Albalawi, 2021d).…”
Section: Preparing Of Extractmentioning
confidence: 99%